Importin-α7 Is Involved in the Formation of Ebola Virus Inclusion Bodies but Is Not Essential for Pathogenicity in Mice - Gabriel, Gülsah (J Infect Dis, 2015)
Ebola virus (EBOV) protein 24 antagonizes the host interferon (IFN) response by hijacking select nuclear importin-α isoforms. Thereby, it blocks STAT1-mediated IFN-α/β and IFN-γ synthesis. However, owing to the lack of importin-α knockout animal models in the past, their role in EBOV pathogenesis remained largely unknown. Here, we demonstrate that importin-α7 is involved in the formation of EBOV inclusion bodies and replication. However, deletion of the gene encoding importin-α7 was not sufficient to increase survival rates among mice infected with EBOV.